The teacher’s body elements that influence the teaching-learning process of university nursing students - Sérgio da Silva, Paulo; Almeida de Figueiredo, Nébia Maria (Investigación y Educación en Enfermería, 2017)
Objective. To identify the body elements of the teacher that influence the teaching-learning process and to analyze their effects on university nursing students. Methods. Qualitative research with descriptive approach implemented through a dramatic play dynamics. In the second half of 2015, sixteen students from a private university center located in Rio de Janeiro (Brazil) participated in the study. The data processing was carried out by using Bardin’s theoretical and analytical framework. Results. Four decoding units were created. They verse about the teacher’s positioning, body movements, eyes, facial expressions as well as the clothes used to teach nursing. Conclusion. The teacher’s elements are capable of generating effects that influence the process of learning nursing. This leads us to believe that the body should continue to be an object of study and discussion in the higher education of nurses. How to cite this article: Silva PS, Figueiredo NMA. The teacher’s body elements that influence the teaching-learning process of university nursing students. Invest. Educ. Enferm. 2017; 35(3): 268-275.